Risk premia in the German electricity futures market - Matthäus Pietz (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
The mechanism behind price formation in electricity futures markets is still under discussion. Theory suggests that hedging pressure caused by deviating risk preferences is the most promising approach. This paper contributes to this discussion through an empirical investigation of electricity futures for delivery in Germany traded at the European Energy Exchange (EEX). We analyse the futures prices from an ex post perspective and show that there is evidence for significant positive risk premia at the short-end. Furthermore, we find that risk premia show a term structure. Evidence for the existence of seasonality in the risk premia is found as well. When testing for factors influencing the risk premia the results suggest that risk premia are directly related to factors linked to risk considerations.
Keywords: G13; L94; Q40; 330; Electricity; Electricity Market; Forward Market; Futures Market; Risk Premia; Risk Premium; Realised Risk Premia; Ex post Risk Premia; Energiemarkt; Termingeschäft; Risikoprämie; Stromhandel; Deutschland